Education and emancipation, educational policies and «de-emancipation»: A history of the Nigerian education system from 1914 to 2014 - Grace Oluremi Akanbi; Alice Arinlade Jekayinfa (Espacio, Tiempo y Educación, 2019)
Nigeria as a nation came into being in the year 1914 through the amalgamation of the Southern and Northern Protectorates by Sir Frederick Lugard. After this amalgamation, and prior to independence, there was no education policy clearly defined by the colonial government; instead, several educational ordinances were promulgated. However, the 1920 Phelps-Stokes Commission awakened the colonial government to the need for improvement. The 1951 regionalisation of education laws that later emerged and their implementation also focused on mass literacy and theoretical education. The exposure to higher education by few Nigerians, however, led to the agitation for independence, which was eventually granted on October 1, 1960. The independence invested Nigerians with the right to take their destiny into their own hands, including the formulation of education policies for the total emancipation of the citizenry. Hence, the 6-3-3-4 system emerged, and the first National Policy on Education (NPE) was officially published in 1977. Unfortunately, the lack of proper implementation of these education policies has continued to «de-emancipate» the citizens of Nigeria. Although the present administration is encouraging patronage of ‘Made in Nigeria’ goods, much still needs to be done to improve education policies, especially in the conceptual framework of functional education. This research is historical, and a historical method was therefore adopted, using both primary and secondary sources of information. Several recommendations are made, including that there is the need for a total overhaul of the Nigeria education system to accommodate effective implementation of policies and monitoring mechanisms for more dynamic and functional education.